Hubungan Dukungan Keluarga Dan Paritas Dengan Keberhasilan Pemberian ASI Eksklusif Ibu Pekerja Di Yogyakarta - Fitriana, Elsha Nur; Hutasoit, Masta (NHM PRESS, 2023)
Exclusive breastfeeding gives breast milk to babies aged 6-24 months without any other food or drink. The aspect of occupation is the reason why mothers do not give exclusive breastfeeding to babies. Family support is vital to increase the success of exclusive breastfeeding. This research aims to know the correlation between family support and parity with the success of exclusive breastfeeding for working mothers in Yogyakarta. This research used a cross-sectional design. The population of this research was all working mothers with babies aged 6-24 months in the working area of ​​Puskemas (Community Health Center) Umbulharjo I in 2023 with a total sampling. The analysis results showed that there was no correlation between parity and the success of exclusive breastfeeding with a p-value of 0.656> 0.05. However, there was a relationship between family support and the success of exclusive breastfeeding with a p-value of 0.014 <0.05. There is a correlation between family support and the success of exclusive breastfeeding for working mothers in Yogyakarta. There is no correlation between parity and the success of exclusive breastfeeding for working mothers in Yogyakarta.